Primary health care and mother and child healthcare - Tavera Salazar, Mario (2018)
The Primary Health Care strategy introduced concepts which sought to revolutionize the way how to achieve Health for All at the global level. The Declaration of Alma Ata was a prelude to initiatives and global plans that sought compromise to States and society in achieving access to health equity. The Summit of Action for Children and the Meeting of the Millennium, which agreed health targets to achieve by year 2015 were inspired by the concepts included in Primary Health Care. While it is true that the purposes lying below the postulates in Alma Ata were not reached, there was remarkable progress in aspects related to the Mother and Child Health. The Selective Primary Healthcare inspired the so-called “Revolution for the Child Survival”, which identified the main causes of the 15 million deaths in children recorded at the global level at the beginning of the Decade of the eighties of the last century, as well as the simple, low-cost interventions based on the evidence shown to be effective in the prevention of this “silent emergency” represented by the avoidable child deaths. Product of these interventions related to children health and the subsequent inclusion of interventions for the prevention of the 500 000 preventable maternal deaths recorded worldwide at the beginning of this century, has achieved remarkable progress at global level. Peru was one of the countries of the Americas that showed greater progress in reducing maternal and infant mortality. This article seeks to find an explanation of procedures and processes that allowed these achievements at the global level and in Peru, inspired by the principles proposed by the Primary Health Care strategy.